Regional Development and Decentralization - Two Options to Overcome Lack of Funding - Dubravka Jurlina Alibegovic; Suncana Slijepcevic; Zeljka Kordej-De Villa (European Regional Science Association (ERSA), 2013)
Decentralization can be generally described as a process in which selected functions are assigned to sub-national units. The literature identifies number of positive consequences of decentralization which all lead to better satisfaction of citizens? needs for public services. Although decentralization process in Croatia started more than 10 years ago, it still has not been finished. It led to new division of authorities and responsibilities to the local government units, but the level of fiscal decentralization remained lower than in the EU countries. The efficient decentralization should incorporate delegation of authorities, responsibilities and resources to local government units based on the clear criteria, but also should ensure better coordination and cooperation of all entities in providing public functions. In the paper we analyze fiscal capacity of local government units to provide an insight into the main problems of decentralization in Croatia. We show that the most of local government units have very low fiscal capacity and cannot finance basic public functions from their own resources. The paper also presents result of the performed survey about decentralization process among local councilors at the regional level in Croatia. We explore how local councilors at regional level in Croatia evaluate different goals of decentralization. Having in mind the lack of fiscal capacity, we identify two possible solutions for an optimal provision of public functions. The first one is level of political will for the joint provision of public functions between different local units, and the second one is change in territorial division of the country. We measure the difference in the attitudes toward these questions across counties.
Keywords: 330; decentralization; fiscal capacity; regional development; Croatia